Exploring the Evolution of Indonesian Poetry: A Comparative Analysis of Classical and Contemporary Expressions - Silalahi, Masna; Simbolon, Wasdo; Simbolon, Kojek (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
This research delves into the heart of Indonesian culture and literature through a comparative analysis of classical and contemporary Indonesian poetry. Indonesian poetry, a dynamic and culturally significant form of artistic expression, provides a unique lens through which to explore the evolution of a nation's identity, artistry, and engagement with the globalized world. This research examines the continuities and innovations between classical and contemporary Indonesian poetry, highlighting themes, linguistic features, and cultural influences. In the classical realm, Indonesian poetry, rooted in the Hindu-Buddhist Majapahit Empire, presents themes of courtly love, epic narratives, and archaic linguistic elements. These age-old traditions, echoing the rhythms of history, have remained pivotal in preserving the cultural heritage of Indonesia. In the contemporary arena, Indonesian poetry reflects a nation in flux, grappling with questions of national identity, social justice, and the impact of globalization. Contemporary poets employ linguistic innovations and utilize digital platforms, making Indonesian poetry accessible to a global audience while advocating for societal change. This research underscores the cultural, social, and historical significance of both classical and contemporary Indonesian poetry. It explores how these poetic traditions have been integral in preserving Indonesian culture, shaping its identity, and engaging with the complexities of the modern world. The findings of this research offer a profound understanding of the enduring power of literature to reflect and inspire cultural evolution.